The glycolytic enzyme ALDOA and the exon junction complex protein RBM8A are regulators of ribosomal biogenesis - Schwarz, Jessica Denise; Lukassen, Sören; Bhandare, Pranjali; Eing, Lorenz; Snaebjörnsson, Marteinn Thor; García, Yiliam Cruz; Kisker, Jan Philipp; Schulze, Almut; Wolf, Elmar (Frontiers in Cell and Developmental Biology, 2022)
Cellular growth is a fundamental process of life and must be precisely controlled in multicellular organisms. Growth is crucially controlled by the number of functional ribosomes available in cells. The production of new ribosomes depends critically on the activity of RNA polymerase (RNAP) II in addition to the activity of RNAP I and III, which produce ribosomal RNAs. Indeed, the expression of both, ribosomal proteins and proteins required for ribosome assembly (ribosomal biogenesis factors), is considered rate-limiting for ribosome synthesis. Here, we used genetic screening to identify novel transcriptional regulators of cell growth genes by fusing promoters from a ribosomal protein gene (Rpl18) and from a ribosomal biogenesis factor (Fbl) with fluorescent protein genes (RFP, GFP) as reporters. Subsequently, both reporters were stably integrated into immortalized mouse fibroblasts, which were then transduced with a genome-wide sgRNA-CRISPR knockout library. Subsequently, cells with altered reporter activity were isolated by FACS and the causative sgRNAs were identified. Interestingly, we identified two novel regulators of growth genes. Firstly, the exon junction complex protein RBM8A controls transcript levels of the intronless reporters used here. By acute depletion of RBM8A protein using the auxin degron system combined with the genome-wide analysis of nascent transcription, we showed that RBM8A is an important global regulator of ribosomal protein transcripts. Secondly, we unexpectedly observed that the glycolytic enzyme aldolase A (ALDOA) regulates the expression of ribosomal biogenesis factors. Consistent with published observations that a fraction of this protein is located in the nucleus, this may be a mechanism linking transcription of growth genes to metabolic processes and possibly to metabolite availability.